Indoor air pollution and its association with poor lung function, microalbuminuria and variations in blood pressure among kitchen workers in India: a cross-sectional study - Amarnath Singh; Chandrasekharan Nair Kesavachandran; Ritul Kamal; Vipin Bihari; Afzal Ansari; Parappurath Abdul Azeez; Prem Narain Saxena; Anil Kumar KS; Altaf Hussain Khan (BMC, 2017)
Abstract Background The present study is an attempt to explore the association between kitchen indoor air pollutants and physiological profiles in kitchen workers with microalbuminuria (MAU) in north India (Lucknow) and south India (Coimbatore). Methods The subjects comprised 145 control subjects, 233 kitchen workers from north India and 186 kitchen workers from south India. Information related to the personal and occupational history and health of the subjects at both locations were collected using a custom-made questionnaire. Worker lung function was measured using a spirometer. Blood pressure was monitored using a sphygmomanometer. Urinary MAU was measured using a urine analyzer. Indoor air monitoring in kitchens for particulate matter (PM), total volatile organic compounds (TVOC), carbon dioxide (CO2) and carbon monoxide (CO) was conducted using indoor air quality monitors. The size and shape of PM in indoor air was assessed using a scanning electron microscope (SEM). Fourier transform infrared (FTIR) spectroscopy was used to detect organic or inorganic compounds in the air samples. Results Particulate matter concentrations (PM2.5 and PM1) were significantly higher in both north and south Indian kitchens than in non-kitchen areas. The concentrations of TVOC, CO and CO2 were higher in the kitchens of north and south India than in the control locations (non-kitchen areas). Coarse, fine and ultrafine particles and several elements were also detected in kitchens in both locations by SEM and elemental analysis. The FTIR spectra of kitchen indoor air at both locations show the presence of organic chemicals. Significant declines in systolic blood pressure and lung function were observed in the kitchen workers with MAU at both locations compared to those of the control subjects. A higher prevalence of obstruction cases with MAU was observed among the workers in the southern region than in the controls (p < 0.01). Conclusions Kitchen workers in south India have lower lung capacities and a greater risk of obstructive and restrictive abnormalities than their north Indian counterparts. The study showed that occupational exposure to multiple kitchen indoor air pollutants (ultrafine particles, PM2.5, PM1, TVOC, CO, CO2) and FTIR-derived compounds can be associated with a decline in lung function (restrictive and obstructive patterns) in kitchen workers with microalbuminuria. Further studies in different geographical locations in India among kitchen workers on a wider scale are required to validate the present findings.